Scalable Data Integration for Real-Time Patient Care: A Compliance and Cybersecurity Perspective - Avinash Mavireddi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In the evolving landscape of modern healthcare, real-time data integration has emerged as a critical component for delivering optimal patient care while maintaining robust security and regulatory compliance. This comprehensive article explores the implementation strategies, challenges, and outcomes of healthcare data integration systems across diverse clinical settings. The article examines the impact of integrated systems on clinical workflows, patient outcomes, and operational efficiency while addressing the complex requirements of data security and regulatory compliance. Through detailed case studies of large hospital networks and rural healthcare providers, this article demonstrates how strategic implementation of integrated healthcare systems can transform care delivery, enhance patient outcomes, and optimize resource utilization. The findings provide valuable insights for healthcare organizations at various stages of their digital transformation journey, offering evidence-based strategies for successful system implementation and optimization.